Disfunção temporomandibular: alterações funcionais quanto à postura e flexibilidade cranio-cervical, atividade eletromiográfica da musculatura mastigatória, qualidade de vida e síndrome de burnout - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Introduction: The temporomandibular disorder (TMDs) is a broad term for changes and clinical problems involving temporomandibular joints (TMJ), the muscles of mastication and other associated structures. With pathophysiology not yet fully understood and with a multifactorial etiology, TMD is one of the most common causes of orofacial pain and one of the major causes of musculoskeletal pain. Objective: This study aims to verify the association between TMD, diagnosed through the Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD), with Burnout Syndrome (SB), craniocervical posture, cervical range of motion , (EMGs) of the masseter and temporalis muscles, as well as to verify the impact of TMD on quality of life related to oral health (HRQoL). Methodology: The present work is an observational, transversal, prospective and quantitative approach, of applied nature, regarding the goals and exploratory. The sample consisted of 50 women, aged between 18 and 40 years, with TMD according to RDC / TMD, who met the established inclusion and exclusion criteria. The evaluation instruments were RDC / TMD, Maslach Burnout Inventory - General Survey, Oral Health Impact Profile (OHIP-14), cervical fleximetry, biophotogrammetry and EMGs. Results: The mean age of the sample was 27.48 ± 6.37 years. Regarding oral health, the sample had between 24 and 32 teeth and 76% reported bruxism. In relation to TMD, 66% had mixed TMD, 30% TMD muscle and 4% TMD joint. Regarding SB, there were no differences in the domain scores between the various TMD diagnoses. The higher the joint involvement, the higher the SB scores in the areas of emotional exhaustion and depersonalization. The group with greater degree of chronic pain presented higher emotional exhaustion score for SB. The higher the score for SB the worse is the HRQoL and the greater degree of depression. The postural angles were not different between the TMD diagnoses and had no correlation with the limitations related to the mandibular function. The diagnosis of muscular and mixed TMD had lower right cervical rotation compared to joint diagnosis. The HRQoL scores did not differ from the diagnosis of TMD. The groups with the highest degree of chronic pain presented worse QRSRS. Joint involvement on one side or biarticular had worse QRSRS than the group without joint involvement. A greater degree of pain, lower mandibular opening, greater limitation related to mandibular function and greater depression implied a worse HRQoL. Whether or not bruxism presented, there is no difference in the HRQoL. Participants divided into types of diagnoses and those divided in presence and absence of bruxism did not present differences in EMGs values. The prevalence in muscle activation did not imply differences in the limitations related to mandibular function, as there was no correlation between this and EMGs values. The grade of chronic pain I and II presented significantly lower values of left temporal GEMS in comparison with the participants without pain. Conclusion: Muscular impairment in TMD exerts influence on fleximetry/ range of motion of the neck. Joint involvement, depression, degree of chronic pain and limitations of mandibular function have an impact on HRQoL. A worse HRQoL is accompanied by a worse SB score and it is impacted by joint impairment and depression. The various TMD diagnoses showed no differences in the EMG activity as well as in the craniocervical posture.
Keywords: Esgotamento profissional; Postura; Eletromiografia; Amplitude de movimento articular; Síndrome da disfunção da articulação; Temporomandibular; Qualidade de vida; Professional exhaustion; Posture; Electromyography; Extent of articular motion; Temporomandibular joint dysfunction syndrome; Quality of life; CNPQ::CIENCIAS DA SAUDE